EXPECTED OCCURRENCE OF THE BLIND ORE BODIES AT THE LOWER LEVELS OF THE BALEI DEPOSIT AND A MECHANISM OF THE RICH ORES FORMATION AT THE NEAR-SURFACE GOLD-SILVER ORE DEPOSITS - E. M. Nekrasov (Известия высших учебных заведений: Геология и разведка)
The gold ore chimneys of 2 types have been shown to be developed at the near-surface deposits of gold and silver ores. These types are: 1 - bulk ones, of the vein-nested-veinlet ore bodies of stockwork shapes and 2 - small pay streaks of the ore bodies, appeared either in single veins or in the veins, being a part of the wide ore bundles. The example of the first type is the Central ore column of Balei deposit and the column of the Glavnaya (Main) vein of the Karamkenskoe deposit. A deiailed analyses of the graphic material, made by N.V. Petranovskaya for Balei deposit, confirms, that under the bottom of the ore controling vein №2 in the vertical interval from 100 to 250-350 m the rich ores can be prevailed in the zones, which are likely to join with ore bodies of Taseevsky site. The discovery of the new bulk gold ore chimnies is likely to be there. With this, an additional exploration of the south-east flanks of the Balei deposit is needed, that can lead to the discovery of the new bulk gold ore chimnies.